1976
DOI: 10.1111/j.1471-0528.1976.tb00770.x
|View full text |Cite
|
Sign up to set email alerts
|

Adenocarcinoma of the Uterine Cervix: Cytological Evidence of a Long Preclinical Evolution

Abstract: Adenocarcinoma of the cervix occurred in 13 women who had previously had 'negative' cervical smears. These smears were reviewed, and abnormalities were found in six cases, the intervals ranging from two to eight years. It is concluded that adenocarcinoma, like squamous carcinoma of the cervix, can have a prolonged evolution during which it is cytologically detectable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
14
1
2

Year Published

1982
1982
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 3 publications
0
14
1
2
Order By: Relevance
“…In 18 (42%) patients, the smear was normal, including four of five cases in which the cancer was occult. In a review of previous negative smears in 13 women with invasive adenocarcinoma, Boddington et al 7 found abnormalities in smears from 6 patients 2 to 8 years before diagnosis. In these cases the Ayre spatula alone was used.…”
Section: Discussionmentioning
confidence: 99%
“…In 18 (42%) patients, the smear was normal, including four of five cases in which the cancer was occult. In a review of previous negative smears in 13 women with invasive adenocarcinoma, Boddington et al 7 found abnormalities in smears from 6 patients 2 to 8 years before diagnosis. In these cases the Ayre spatula alone was used.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17][18] With the advent of superior endocervical sampling, cytologists are presented with glandular and squamous precursor lesions characterized by cells that are sometimes smaller and less differentiated than those previously experienced. These presentations are similar to the native epithelium in the upper endocervical canal, sometimes with tubal or tuboendometrial metaplasia, and from cells inadvertently procured from the endometrium.…”
Section: Discussionmentioning
confidence: 99%
“…Precise data on incidence and survival rates of early stage adenocarcinoma are not available because of different definitions and diagnoses and because of limited follow-up information. 1'v17- 20 In this series, the criteria of early stage adenocarcinoma were defined strictly. In order to exclude the influence of squamous cell carcinoma or undifferentiated carcinoma components, and to investigate the nature and histogenesis of the "pure" type of early stage adenocarcinoma, cases coexisting with invasive squamous cell carcinoma (including microinvasive squamous cell carcinoma) or with undifferentiated carcinoma, were excluded from the category of early stage adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%